2012
DOI: 10.1108/03090561211260013
|View full text |Cite
|
Sign up to set email alerts
|

Sensory description labels for food affect consumer product choice

Abstract: PurposeThis observational study set out to investigate the effect of sensory description labels on consumer choice of apples in a grocery retail store.Design/methodology/approachAn independent observation study was conducted in a retail grocery store setting. A total of 1,623 consumers were observed over a four‐day period in four different sessions, each using three apple varieties (JONAGOLD, INGRID MARIE, and ELISE). Marketing strategies differed between the sessions as follows: sort name labelling only, sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…However, a previous study that confirmed sensory descriptors to be important when purchasing wine also demonstrated that consumers struggled to match these descriptors with corresponding wines (Charters et al, 2000), and untrained consumers have been found incapable of matching wine descriptors with a corresponding wine (d 'Hauteville, 2003;Weil, 2007). A study by Swahn et al (2010) investigating the effect of sensory descriptors on apple choice found that consumer preference rankings differed when they sampled the apples versus when they relied solely on sensory descriptors to make their choice. These findings call into question the necessity of sensory descriptors, especially in tasting rooms.…”
Section: Tasting Sheet Sensory Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous study that confirmed sensory descriptors to be important when purchasing wine also demonstrated that consumers struggled to match these descriptors with corresponding wines (Charters et al, 2000), and untrained consumers have been found incapable of matching wine descriptors with a corresponding wine (d 'Hauteville, 2003;Weil, 2007). A study by Swahn et al (2010) investigating the effect of sensory descriptors on apple choice found that consumer preference rankings differed when they sampled the apples versus when they relied solely on sensory descriptors to make their choice. These findings call into question the necessity of sensory descriptors, especially in tasting rooms.…”
Section: Tasting Sheet Sensory Descriptorsmentioning
confidence: 99%
“…In a winery tasting room, on the other hand, consumers are encouraged to try many different wines before purchasing. A consumer's decision when supplied with samples, as opposed to just sensory descriptors, may not be the same, as suggested by Swahn et al (2010). There has been no research to determine the effect that sensory descriptors provided with product samples have on consumer choice.…”
mentioning
confidence: 99%
“…Descriptive food names have been shown to influence consumer liking and function as a signal of food quality (Wansink, van Ittersum & Painter, 2005). Furthermore, signalling sensory characteristics has been shown to influence food choice (Swahn, Mossberg, Öström & Gustafsson, 2012), which is a practice frequently used by the wine industry (Dimara & Skuras, 2005;Herdenstam, Hammarén, Ahlström & Wiktorsson, 2009). Depending on context, descriptive food names, flavour descriptors and names of food dishes and ingredients may signal credence and create expectations, in turn affecting hedonic liking.…”
Section: Descriptive Food Namesmentioning
confidence: 99%
“…Labelling effectiveInformation: Copy/illustrations on use The Packaging Federation, 1993;Vidales Giovanetti, 1995;Nancarrow et al 1998Rundh, 2005Davies & Wright, 1994;Swahn et al, 2012Rundh, 2005Lee et al, 1991;Nancarrow et al 1998 Marketing al., 1991al., Lee et al, 1991Nancarrow et al, 1998}Rundh, 2005Rundh, 2005The Packaging Federation, 2004;Lee et al, 1991 The Packaging Federation, 2004…”
Section: Core Functions/roles Elements Of Packaging's Role Literaturementioning
confidence: 99%